1990
DOI: 10.1557/jmr.1990.2882
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the structure and stability of the Pt/SiC(001) interface

Abstract: Auger electron spectroscopy and low energy electron diffraction have been applied to the study of the structure and thermal stability of the Pt/j3-SiC(001) interface. The morphology of the interface appears to be governed by the competition among surface diffusion, intermixing, and chemical reaction. An ultrathin Pt layer (=S8 A thick) deposited on a substrate at low temperature is laterally uniform with some degree of intermixing across the interface. Brief anneals at =Sl000 °C result in aggregation of the Pt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…Figure 2c represents the islands scattering on the surface of the sample annealed at 600 °C for 10 min. This result agrees with the work of Bermudez et al (1990), where Pt films (≤0.8 nm thick) were deposited on cubic β-SiC (001) surfaces, and also compatible with the case of a Pd film on a SiC substrate (Veuillen et al , 1999; Tsiaoussis et al , 2007). The reason for the island growth on a SiC single crystal substrate may come from crystal lattice mismatch at the interface and inhomogeneous stress induced by the thermal process of the Pt/SiC interface.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Figure 2c represents the islands scattering on the surface of the sample annealed at 600 °C for 10 min. This result agrees with the work of Bermudez et al (1990), where Pt films (≤0.8 nm thick) were deposited on cubic β-SiC (001) surfaces, and also compatible with the case of a Pd film on a SiC substrate (Veuillen et al , 1999; Tsiaoussis et al , 2007). The reason for the island growth on a SiC single crystal substrate may come from crystal lattice mismatch at the interface and inhomogeneous stress induced by the thermal process of the Pt/SiC interface.…”
Section: Resultssupporting
confidence: 91%
“…Pt can react with SiC to form Pt-silicides: Pt 3 Si, Pt 12 Si 5 , Pt 2 Si, Pt 6 Si 5 , and PtSi (Rijnders et al , 1997; Xu et al , 2008). Papanicolaou et al (1989) and Bourenane et al (2007) reported that Pt is used for the fabrication of a good Schottky contact with a SiC single-crystal substrate throughout the annealing sequence, and studies of interface electrical property of Pt/SiC joints revealed that the contact resistivity depends on annealing parameters, thickness of a Pt film and phases involved at the interfaces (Bermudez et al , 1990; Chen et al , 1994; Porter and Davis, 1995). An increase of Schottky barrier height (SBH) can be controlled from the grain growth and the film homogeneity at the surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…A similar behavior has been also observed for the Co/6H-SiC and Pt/ ␤-SiC͑100͒ interfaces where free carbon is released after silicide formation. 12,18 Upon low oxygen exposures, we observe that the peak N/peak M intensity ratio decreases indicating the decrease of these carbon species present at the surface. This behavior is likely resulting from CO and/or CO 2 formation and desorption into the vacuum as previously reported for alkali metal ͑Rb͒ room temperature promoted oxidation of the ␤-SiC͑100͒ surface.…”
Section: B Na/␤-sic(100)mentioning
confidence: 85%
“…6,7 In contrast, the formation of metal/silicon carbide interfaces has been investigated for several systems with various metal adsorbates having very different properties and including transition metals, [8][9][10][11][12] aluminum, 13,14 full or almost full d-band metals. [15][16][17][18] However, in most of these studies, rather thick metal films were used in order to explore the thermal stability of metallic contacts. Room temperature metal/SiC reactive interface formation was found to take place for Au, Ni, Pd, Ti, W, Mo, and Ta while for Pt, Sn, Al, and Co a reaction took place only above room temperature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation